Pengaruh kepimpinan sekolah dan kepuasan komunikasi terhadap pengurusan konflik guru generasi Y di sekolah menengah kebangsaan Negeri Kedah - Marlia, Jamail (2020)
The quality of educational development depends on the capacity of teacher leadership that can motivate the advancement of students as dedicated in the Malaysia Education Blueprint (MEB, 2013-2025). Nevertheless, teacher leadership issue that is not given attention and ineffective communication trigger conflicts in the school environment, which in turn impedes the empowerment of teacher leadership. This research intended to identify the level of teacher leadership, communication satisfaction and conflict management in secondary schools. Furthermore, the study attempted to examine the influence of communication satisfaction as a mediator on the relationship between teacher leadership and conflict management. Cross-sectional survey methods were used in collecting study data. Instruments employed included Distributed Leadership Scale, Communication Satisfaction Questionnaires and Rahim Organizational Conflict Inventory (Form A). 370 generation Y teachers in secondary schools in Kedah State were involved in this study where quantitative data of the study were analyzed with t-test statistics, Analysis of Variance (ANOVA), Pearson correlation and multiple regression analysis using the Statistical Package for Social Science (SPSS). The outcomes revealed that all the variables indicated a high level and significant relationship. Communication satisfaction performed a function as a mediator on the relationship between teacher leadership and conflict management. This research confirmed that high levels of teacher leadership and communication satisfaction impacts conflict management towards the growth of better quality education. Ergo, the 3K domain: Leadership, Communication and Conflict, should be highlighted because generation Y teachers can also empower high-performing leadership in every school to develop effective schools.